Agricultural land: Inequality and insecurity - Lambrecht, Isabel B.; Belton, Ben; Fang, Peixun; Minten, Bart; Naing, Phyo Thandar (International Food Policy Research Institute, 2024)
Land is indispensable to agricultural production and, thus, a critical resource in sustaining agriculture-based livelihoods. Moreover, land as property may facilitate access to credit when used as collateral, further facilitating productive activities. Land ownership also constitutes a buffer against shocks, as it can often be rented out, mortgaged, or sold when cash needs are high.